2018
DOI: 10.1016/j.joule.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Firm Low-Carbon Electricity Resources in Deep Decarbonization of Power Generation

Abstract: Full decarbonization of the electricity sector is critical to global climate mitigation. Across a wide range of sensitivities, firm low-carbon resources-including nuclear power, bioenergy, and natural gas plants that capture CO 2 -consistently lower the cost of decarbonizing electricity generation. Without these resources, costs rise rapidly as CO 2 limits approach zero. Batteries and demand flexibility do not obviate the value of firm resources. Improving the capabilities and spurring adoption of firm low-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
206
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(250 citation statements)
references
References 37 publications
11
206
0
1
Order By: Relevance
“…In stark contrast, Buongiorno et al [16] found that excluding nuclear power would double or triple the average electricity cost for deep decarbonization. Similarly, Sepulveda et al [17] concluded that firm lowcarbon resources, such as nuclear power, might reduce the electricity cost by 10%-62% across fully decarbonized cases. Many other studies have analyzed a renewable future electricity system (without nuclear) in Europe and found that the low-carbon electricity system can be achieved with modest cost increase as compared with the current cost [5,6,[18][19][20].In the case of Sweden, several recent publications [21][22][23] have evaluated the economic impact of nuclear power exiting the Swedish electricity system and investigated the potential options to replace nuclear power.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In stark contrast, Buongiorno et al [16] found that excluding nuclear power would double or triple the average electricity cost for deep decarbonization. Similarly, Sepulveda et al [17] concluded that firm lowcarbon resources, such as nuclear power, might reduce the electricity cost by 10%-62% across fully decarbonized cases. Many other studies have analyzed a renewable future electricity system (without nuclear) in Europe and found that the low-carbon electricity system can be achieved with modest cost increase as compared with the current cost [5,6,[18][19][20].In the case of Sweden, several recent publications [21][22][23] have evaluated the economic impact of nuclear power exiting the Swedish electricity system and investigated the potential options to replace nuclear power.…”
mentioning
confidence: 99%
“…Germany, Belgium, and Switzerland have decided to phase out nuclear power, while Finland and France are building new nuclear power plants.The cost difference for decarbonizing the electricity system with and without nuclear power has been subject to recent debate in the scientific community [9][10][11][12]. Some studies show that excluding nuclear power increases the electricity system cost modestly [13][14][15], while others claim that the increase in cost is substantial [16,17]. Jägemann et al [13] investigated the decarbonization pathways of the European electricity sector and found that the total electricity system cost, together with the cost of decarbonization, would increase by 11% if nuclear power and carbon capture and storage (CCS) were excluded.…”
mentioning
confidence: 99%
“…Using dispatchable generation and reducing the share of intermittent electricity in the system has the potential to reduce system costs significantly and allows for a more efficient use of local VRES. 59 At future cost estimates of electricity generation from WWS fuels, these fuels would be competitive to VRES at a renewable share of about 80% or above in most scenarios (Fig. 3).…”
Section: Driver 3: Economics Of Renewable Energy Systemsmentioning
confidence: 99%
“…Many existing studies of high wind and solar penetration assess the role of a couple of drivers in isolation or with a limited number of joint sensitivities (e.g. Fell and Linn 2013, Shearer et al 2014, Hirth 2015, MacDonald et al 2016, Craig et al 2018, Eshraghi et al 2018, Sepulveda et al 2018, as shown in SI appendix, table 1. Although these one-way sensitivities are valuable ceteris paribus experiments, they do not comprehensively assess the relative impact of a range of factors by jointly varying all drivers simultaneously.…”
Section: Introductionmentioning
confidence: 99%